(untitled) (ACME, 2021)
The city of Ashqelon lies on the southern part of the Israeli coast, 50 km south of Jaffa, and 13 km north of Gaza. It was a relevant port city during Antiquity, until the Crusaders and the Arab conquest in the 13th century when it was destroyed and abandoned. The continuity of the settlement resulted in a rich archaeological deposit, spanning from the Bronze Age to the Medieval period. Still, at the same time, it also caused the dismantling of several buildings and the reuse of architectural debris in the city itself or elsewhere, mostly in other sites along the coast. This paper deals with the spolia of the Roman town, and aims to evaluate the management of the dismantling process in the post-Classical era, the purposes and dynamics of the reuse as well as its geographical spread.